Natural Capital & Corporate Sustainability - Singh, Mitrabinda (Banaras Hindu University, 2010)
Shift happens though people cannot accept it or take time to accept it. Many of the past literatures on corporate sustainability never speak aloud of or, remain silent on Corporate Environmental sustainability. Some of them even argue that the natural stock/capital remains stable all the time. But, the ongoing changes and disasters like Tsunami, water and food shortage, climate change, inequalities and so on cannot be ignored. In fact, the figure shows the corporations realising the environmental issues in Business and interested to contribute to save the nature so as to get the global competitiveness. This conceptual paper provides insight of corporate environmentalsustainability and natural capital with clear definitions and it has also tried to answer the question “Why corporations need to be responsible or accountable towards sustaining the natural capital?” through case study discussions. The benefits that corporations get while going green and the underlying limitations and challenges towards environmental sustainability has also been analysed critically.